2013
DOI: 10.3126/nepjoph.v5i1.7823
|View full text |Cite
|
Sign up to set email alerts
|

Vitreo-retinal disorders at high altitude in Nepal

Abstract: Introduction: Nepal has many mountains including the highest one in the world. People living in high altitude are often involved in climbing mountains. Objective: To explore the pattern of vitreo-retinal disorders at high altitude in Nepal. Materials and methods: Consecutive patients aged 40 years and older who presented at the micro-surgical eye camp at Lukla of Solukhumbu district (2,860 metres) were included. Detailed ocular and systemic histories and ocular examination including dilated fundus evaluation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Indeed, hypoxia‐induced changes in the eye are less evident as acclimatization progresses (Bosch et al., 2010). A survey of vitreoretinal disorders of Sherpas living at high altitude in Nepal reported that high altitude retinopathy without and with dry, age‐related macular degeneration accounted for 16 and 3.7% of vitreoretinal disorders, respectively, in a population of 81 patients (Thapa, Paudyal, Crandall, & Tabin, 2013). Solar retinopathy accounted for only 2.5% of the disorders.…”
Section: Hypobaric Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, hypoxia‐induced changes in the eye are less evident as acclimatization progresses (Bosch et al., 2010). A survey of vitreoretinal disorders of Sherpas living at high altitude in Nepal reported that high altitude retinopathy without and with dry, age‐related macular degeneration accounted for 16 and 3.7% of vitreoretinal disorders, respectively, in a population of 81 patients (Thapa, Paudyal, Crandall, & Tabin, 2013). Solar retinopathy accounted for only 2.5% of the disorders.…”
Section: Hypobaric Environmentmentioning
confidence: 99%
“…Indeed, hypoxia-induced changes in the eye are less evident as acclimatization progresses(Bosch et al, 2010). A survey of vitreoretinal disorders of Sherpas living at high altitude in Nepal reported that high altitude retinopathy without and with dry, age-related macular degeneration accounted for 16 and 3.7% of vitreoretinal disorders, respectively, in a population of 81 patients(Thapa, Paudyal, Crandall, & Tabin, 2013). Solar retinopathy accounted for only 2.5% of the disorders.The frequent high-altitude-related changes of the retina are commonly known as high-altitude retinopathy and may be the result of a combined effect of systemic hypoxia and increased blood viscosity (Barthelmes et al, 2011; Wiedman & Tabin, 1999).…”
mentioning
confidence: 99%